The influence of linguistic listening on eloquence and dialects in the work of Abdelrahman Hadj Salah - djidel, hamza (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract This study aims to reveal the concept of eloquence through the induction carried out by Abd al-Rahman Haj Saleh of the ancient linguistic heritage and to identify the foundations that he approved through reformulating and formulating traditional curricula, which were based on controls and standards that contributed to identifying some linguistic concepts and highlighting a new vision for modern linguistic issues, especially listening. The linguist and his role in building the foundations of linguistic eloquence, which was manifested in defining a new vision of the audio content in the ancient linguistic lesson so that the modern linguistic lesson intersects with linguistic listening in the light of the ancient linguistic heritage, in addition to revealing the points of contact between the auditory and its impact on the standards of eloquence, old and new.